Case report: Uncommon gastric metastasis as a presentation of recurrent clear cell renal cell carcinoma - Sabaté-Ortega, Josep; Albert-Carrasco, Marc; Escribano-Ferrer, Carmen; Grau-Manrubia, Gerard; Fina-Planas, Clàudia; López-Núñez, Carme; Teixidor-Vilà, Eduard; Bujons-Buscarons, Elisabet; Montañés-Ferrer, Clàudia; Sala-González, Núria (Frontiers in Oncology, 2024)
Renal cell carcinoma (RCC) is a kidney neoplasm that accounts for 85% of cases and has complex genetic pathways that affect its development and progression. RCC metastasis can occur in 20%-50% of patients and usually affects distant organs. Gastric metastases (GM) from RCC are rare and present as polyp-like growths in the submucosal layer, accounting for 0.2%-0.7% of cases. This case report describes an 84-year-old female with Furhman grade II ccRCC who presented with an atherothrombotic ischemic stroke and gastrointestinal bleeding nine years post-radical nephrectomy. Gastroscopy revealed a 12mm pseudopedicled gastric lesion with ulceration and bleeding, diagnosed as metastatic ccRCC. The discussion focuses on the rarity, diagnostic challenges, and prognostic elements of gastric metastasis from RCC. The median survival after detecting digestive metastasis varies widely, and the mechanisms include direct invasion and dissemination through lymphatic, transcelomic, or hematogenous routes. Prognostic markers encompass patient history, symptoms, time since RCC diagnosis, overall health, and genetic factors. Surgical removal of gastric lesions and targeted therapy are treatment options that can improve survival. This case report highlights the need for further research to enhance diagnostic and treatment strategies for this rare aspect of RCC pathophysiology.